Curtain up! : behind the scenes at the Royal Opera House - O'Hara, Lauren (Thames & Hudson, 2022)
"On opening night of The Nutcracker, the magnificent red velvet curtain is about to rise. The ballet dancers, singers, actors and musicians of the Royal Opera House are warming up in the wings and in the orchestra pit. Backstage, the crew prepares the lights, sets, props and costumes. Open this book and join Figaro the theater cat on a special backstage tour; where--from wigs and hats to scenery painting, ballet rehearsals to the orchestra pit, you'll find out how everyone works together to bring a performance to life."--